Treatment Outcomes and Associated Factors among Patients with Drug-Resistant Tuberculosis (DR-TB) at a Tertiary Government Hospital in Nueva Ecija: A Seven-Year Retrospective Study - Dr Kelvin Clein Curitana (International Journal of Infectious Diseases)
Introduction: DR-TB poses significant challenges to the control and successful eradication and management of TB worldwide. MDR-TB treatment outcome is the most important indicator in WHO's End TB strategy. Tracking of treatment outcomes is essential. In 2020, the Philippines has the highest TB incidence rate in Asia, 4th among 30 high TB burden countries, 7th among high MDR-TB burden countries, one of the 18 countries with more than 80% coverage of rifampicin resistance test, and one among the 10 countries with increased gap between the estimated global incidence of MDR-TB and the number of people enrolled in the treatment. Improving MDR-TB treatment outcomes is one of the five priority actions recommended by WHO to address the global MDR-TB crisis, with a target of 75% treatment success. Methods: A retrospective, observational analysis study design was conducted at the DR. PJGMRMC PMDT STC to all registered patients from July 27, 2015 to December 31, 2021. Patients were assessed for eligibility based on the inclusion and exclusion criteria. The main outcome variable for the study was treatment outcome (five stratum) while the other explanatory variables were the socio-demographic status and the clinical characteristics of DR – TB patients. The study was submitted to Institutional Review Board for ethics assessment and clearance. Data collected were encoded and analyzed using SPSS V25. Descriptive Analysis and multivariate binary logistic regression analysis, Hosmere Lemeshow test and Odds ratios with 95% Confidence intervals were calculated. Results: A total of 399 anonymized patient records were obtained from the ITIS registry and reviewed with only 374 patient records included for the analysis. Among all the patients included, 42.50% cured, 13.10% completed their treatment, 0.30% treatment failure, 8.30% lost to follow-up, and 35.80% died. The overall treatment success rate was 55.60%. Patients who are less than 15 years old, with normal BMI, works in an architecture and construction sectors, received SLOR-FQS regimen, completed treatment for the duration of 6,9,10,20 months, had no or minor adverse drug reactions, and was treated last 2020 had more likely to have successful treatment outcome while those with 1 month treatment and was treated last 2015 were more likely to have unsuccessful treatment outcome. Several other factors had no significant association with treatment outcome. Conclusion: The overall treatment success rate achieved in this study (55.6%) is lower than the values reported from other countries and did not achieve the 75% - 90% target recommended by the WHO. A binary and multivariate logistic regression analyses was done for 22 variables with only 7 variables were independently associated with successful treatment outcome. The lower treatment success rate poses a serious treat for the DOH effort to combat TB and implicates that there are still needs for improvement.